Developing and Validating Assessment Instruments for Community-Based Interprofessional Education - Fairuz, Fairuz; Shafira, Nyimas Natasha Ayu; Aryanty, Nindya; Raudhoh, Siti (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2025)
Background: Interprofessional Education (IPE) prepares health professional students to collaborate effectively and improve patient and community outcomes. Community-based IPE emphasizes authentic learning, cultural sensitivity, and social accountability. This study aimed to develop and validate assessment instruments for evaluating community-based IPE aligned with the Interprofessional Education Collaborative (IPEC) core competencies. Methods : A mixed-methods design was implemented in two stages: instruments development and content validation. Guided by the four IPEC domains, values/ethics, roles and responsibilities, interprofessional communication, and teamwork, three instruments were developed: facilitator assessment, family/community assessment, and peer assessment. Ten experts from medicine, nursing, pharmacy, psychology, and public health evaluated item relevance using a four-point Likert scale. Content validity was analyse using the item-level (I-CVI) and scale-level (S-CVI/Ave) indices. Results: All three instruments demonstrated excellent content validity (I-CVI = 1.00; S-CVI/Ave = 1.00), indicating high expert agreement on relevance and clarity. The multi-source assessment model allows comprehensive evaluation of IPE performance. Facilitator assessments maintain educational standards, family assessments provide patient-centred perspectives, and peer assessments foster reflection, accountability, and teamwork. Conclusion: The validated instruments offer a reliable and context-sensitive framework for assessing IPE competencies in community-based learning. Incorporating multi-source perspectives enhances authenticity and educational alignment, supporting the development of collaborative, ethical, and community-responsive health professionals.